Pyoderma Gangrenosum and Autoimmune Chronic Active Hepatitis in a 17-Year-Old Female. (1988) - Langley, Joanne M.; Roberts, Eve A.; Ipp, Moshe; Laxer, Ronald M.; Boxall, Lionel; Phillips, M. James
Abstract : A 17-year-old girl presented with fever, icterus and painful small nodules on her face and a larger nodular lesion on the left shin. The patient had fatigue, intermittent jaundice and abdominal pain over the preceding three months. The nodular lesions ulcerated and had the typical clinical and histopathological appearance of pyoderma gangrenosum. Although there was no hepatosplenomegaly, serum aminotransferases and immunoglobulin G were elevated; antismooth muscle antibodies were detectable. Inflammatory bowel disease was not presenr. Autoimmune chronic active hepatitis and pyoderma gangrenosum are a rare association and this is the youngest patient in whom the association has been reported.